ANALISIS SIFAT FISIK, KIMIA, MIKROBIOLOGI, DAN DAYA TERIMA ES KRIM SUSU KAMBING DENGAN VARIASI KADAR SUBSTITUSI SUSU KAMBING FERMENTASI TERHADAP SUSU SKIM - , VIKA REVIANA WIDODO, Lily Arsanti Lestari, STP., MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Nowadays, some people have unhealthy diet that can lead them to suffer degenerative disease. Therefore, they have to consume functional food. Goat milkâs benefit become popular now but consumers still donât like its flavor. Goat milk processing becomes preferred product can be done. The food product that can made from goat milk is ice cream with addition of probiotic. This product be expected can give the additional benefits for peopleâs health who consume it. Objective: This study aims to determine the difference of fermented goat milk substitution to skim milk on physical-chemical-microbiological properties and acceptance of goat milk ice cream. Methods: This was an experimental study with Completely Random Design that consist of four variations, 0%, 25%, 50%, and 75% substitution of fermented goat milk to skim milk. Physical properties (color, flavor, taste, viscosity, overrun,melting rate), chemical properties (pH, acidity), and microbiological properties (lactic acid bacteria population) were assessed descriptively. Acceptance was assessed with hedonic test. Result: There were no difference in color and flavor of goat milk ice cream. There were difference on taste, viscosity, overrun, melting rate, pH, acidity, and lactic acid bacteria population. Goat milk ice creams do not have significant differences in color acceptance (p>0,05). Goat milk ice cream have significant difference in flavor, texture, taste, and overall acceptance (p<0,05). Conclusion: There are effects of fermented goat milk substitution to skim milk on physical properties (taste, viscosity, overrun,melting rate), chemical, microbiological, and acceptance (flavor, texture, taste,overall) of goat milk ice cream. There are no effects of fermented goat milk substitution to skim milk on physical properties (color, flavor) and colorâs acceptance of goat milk ice cream.